Influence of covering soybean seeds with bentonite clay on biometric parameters under different irrigation regimes. (Eurasian Journal of Research, Development and Innovation, 2023)
In the bottom article, the effect of encapsulation of soybean seeds with bentonite clays in the amount of 30, 40 and 50 kg/t is shown . on the biometric indicators of the plant under different irrigation regimes.